Microsatellite analysis of the adenomatous polyposis coli (APC) gene and immunoexpression of β catenin in nephroblastoma: a study including 83 cases treated with preoperative chemotherapy. Issue 1 (27th December 2004) - Ramburan, A; Oladiran, F; Smith, C; Hadley, G P; Govender, D
Abstract : Aims: To determine whether microsatellite mutations of the adenomatous polyposis coli (APC) gene have pathological or prognostic significance in nephroblastomas and to correlate APC alterations with β catenin immunoexpression. Methods: One hundred nephroblastomas were analysed, 83 of which received preoperative chemotherapy. Normal and tumour DNA was isolated using standard proteinase K digestion and phenol/chloroform extraction from paraffin wax embedded tissue. Polymerase chain reaction using four APC microsatellite markers—D5S210, D5S299, D5S82, and D5S346—was performed and the products analysed. Immunohistochemistry was performed using the LSAB kit with diaminobenzidine as chromogen. Results were correlated with clinicopathological data using the χ 2 test. Results: Allelic imbalance/loss of heterozygosity was more frequent than microsatellite instability, with 30% of cases showing allelic imbalance/ loss of heterozygosity and 16% showing microsatellite instability. Although there was a significant correlation between the results for individual markers and the clinicopathological data, the overall results do not support a prognostic role for APC in nephroblastoma. Expression of β catenin was seen in 93% of cases. Staining was predominantly membranous, with epithelium, blastema, and stroma being immunoreactive. Cytoplasmic redistribution was seen in 58% of cases, but no nuclear staining was detected. No significant associations between β catenin expression and the clinicopathological parameters were found. Kaplan–Meier survival plots showed that patients with loss of membranous staining and pronounced cytoplasmic staining (score, 3) had a significantly shorter survival (p = 0.04; median survival, 5.87 months). Conclusion: Microsatellite analysis of APC and immunoexpression of β catenin did not provide significant pathological or prognostic information in this cohort of nephroblastomas.